Non thermally-activated transients and buffer traps in GaN transistors with p-type gate: A new method for extracting the activation energy. (November 2020) - Nardo, A.; Meneghini, M.; Barbato, A.; De Santi, C.; Meneghesso, G.; Zanoni, E.; Sicre, S.; Sayadi, L.; Prechtl, G.; Curatola, G.
Abstract: This paper demonstrates that conventional drain current transient (DCT) measurements fail at identifying the correct activation energy of buffer defects in transistors with p-GaN gate. Based on combined pulsed and transient characterization, we demonstrate that (i) under off-state stress, the analysed devices suffer from moderate dynamic-Ron and from positive shift in the threshold voltage; (ii) the de-trapping kinetics, analysed by DCT, are unexpectedly not thermally-activated; (iii) de-trapping kinetics are significantly accelerated when measured at high gate voltage; (iv) we report a power law correlation between the gate leakage measured during the de-trapping phase and the time constant for recovery. Finally, (v) we propose a new characterization procedure, based on TLM structures, to overcome these issues, thus accurately investigating buffer-related effects.